1998
DOI: 10.1002/(sici)1097-4628(19980516)68:7<1077::aid-app5>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Broom fibers as reinforcing materials for polypropylene-based composites

Abstract: Broom fibers have been used as reinforcement for the conventional polypropylene (iPP) and a maleate modified one (iPPMA). A conventional alkaline treatment and a steam explosion extraction process were applied to obtain the cellulosic material from broom branches. Composites were prepared by melt mixing materials with different weight percentages of broom fibers. Also ternary blends (iPPMA/iPP/broom fibers 5/45/50 wt) were obtained to examine the possibility of utilizing the maleate polypropylene as a compatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 2 publications
4
54
0
1
Order By: Relevance
“…It can be found that the crystallinity index of fillers slightly decreases when the alkalization treatment is applied. A similar character of the dependence of cotton or ramie crystallinity during alkali treatment has been reported in recent works [51][52][53]. It is well known that the lignocellulosic fillers undergo three distinct process during mercerization [18,54,55]: fiber swelling, disruption of the crystalline areas and formation of new crystalline lattice after rinsing away the mercerization solution.…”
Section: Waxs Diffraction Analysissupporting
confidence: 74%
“…It can be found that the crystallinity index of fillers slightly decreases when the alkalization treatment is applied. A similar character of the dependence of cotton or ramie crystallinity during alkali treatment has been reported in recent works [51][52][53]. It is well known that the lignocellulosic fillers undergo three distinct process during mercerization [18,54,55]: fiber swelling, disruption of the crystalline areas and formation of new crystalline lattice after rinsing away the mercerization solution.…”
Section: Waxs Diffraction Analysissupporting
confidence: 74%
“…It is expected that removal of hemicellulose will allow better resin penetration and adhesion, since similar results have been obtained using steam exploded broom fibers (Avella et al 1998). The fiber damage imparted by steam explosion would not be expected to be present in straw stems treated with fungi, especially by a fungus that does not degrade significant cellulose (Hadar et al 1993).…”
Section: Determination Of Dominance Of Inoculated Fungusmentioning
confidence: 66%
“…Indeed, steam explosion has been investigated to remove lignin and hemicellulose to allow better resin penetration and adhesion (Avella et al 1998). While significant improvement in interfacial adhesion was seen in steam exploded broom fibers, the extensive physical damage to the fibers imparted by the steam explosion process eliminated any mechanical property improvements.…”
Section: Selective Hawest Of Higher Value Wheat Straw ~Omponentsmentioning
confidence: 99%
“…During the past several years the number of scientifi c work related to the production of Spanish Broom as raw material in the manufacture of composite materials considerably increased (Avella et al, 1998; Angelini et al, 2000; Gabriele et al, 2010; Cerchiara et al, 2010 A). The advantage of Spanish Broom over fl ax and hemp is that it can grow in the most unfavorable limestone soil; it is resilient to draught; and once planted it can be used during a period of up to twenty years, whilst fl ax and hemp demand high quality soil each year.…”
Section: Uvodmentioning
confidence: 99%